PEMBERIAN WASIAT KEPADA AHLI WARIS YANG MENYIMPANG DARI HUKUM ISLAM ( Studi Kecamatan Kutamakmur Aceh Utara ) - PUTRI SARTIKA (PREMISE LAW JURNAL, 2017)
A will or testament is a person’s message for another person who is not his heir; it can be a charitable institution or other institution which does not get the inheritance or excluded from heirs. The result of the research shows that the practice in giving wills to Kuta Makmur Subdistrict is not in accordance with the Islamic law. In its implementation the wills are given when the heirs are absent and without 2 (two) witnesses are also absent when the testimony is uttered. In this case, the requirements for giving a will are not fulfilled and it is given without the consent of the other heirs. The reasons for giving the wills are as follows: 1) giving a will to an heir is considered fair although they equalize the portion between their sons and their daughters, 2) The will is give in order to avoid dispute among the heirs, 3) giving a will has become the custom in this area, and 4) the will is given to the heir who has taken care of his parents during their lives. The status and the amount of the property obtained from the will have to be approved by the other heirs. If the other heirs do not approve and the will is more than 1/3 of the inheritance, the will can be revoked. Keywords: Will, Testement, Heir, Custom